A Multilevel Analysis of Surgical Category and Individual Patient-Level Risk Factors for Postoperative Stroke. (January 2020) - Kummer, Benjamin R.; Hazan, Rebecca; Merkler, Alexander E.; Kamel, Hooman; Willey, Joshua Z.; Middlesworth, William; Yaghi, Shadi; Marshall, Randolph S.; Elkind, Mitchell S. V.; Boehme, Amelia K.
Background and Purpose: Many studies supporting the association between specific surgical procedure categories and postoperative stroke (POS) do not account for differences in patient-level characteristics between and within surgical categories. The risk of POS after high-risk procedure categories remains unknown after adjusting for such differences in patient-level characteristics. Methods: Using inpatients in the American College of Surgeons National Surgical Quality Initiative Program database, we conducted a retrospective cohort study between January 1, 2000, and December 31, 2010. Our primary outcome was POS within 30 days of surgery. We characterized the relationship between surgical- and individual patient-level factors and POS by using multivariable, multilevel logistic regression that accounted for clustering of patient-level factors with surgical categories. Results: We identified 729 886 patients, 2703 (0.3%) of whom developed POS. Dependent functional status (odds ratio [OR]: 4.11, 95% confidence interval [95% CI]: 3.60-4.69), history of stroke (OR: 2.35, 95%CI: 2.06-2.69) or transient ischemic attack (OR: 2.49 95%CI: 2.19-2.83), active smoking (OR: 1.20, 95%CI: 1.08-1.32), hypertension (OR: 2.11, 95%CI: 2.19-2.82), chronic obstructive pulmonary disease (OR: 1.39 95%CI: 1.21-1.59), and acute renal failure (OR: 2.35, 95%CI: 1.85-2.99) were significantly associated with POS. After adjusting for clustering, patients who underwent cardiac (OR: 11.25, 95%CI: 8.52-14.87), vascular (OR: 4.75, 95%CI: 3.88-5.82), neurological (OR: 4.60, 95%CI: 3.48-6.08), and general surgery (OR: 1.40, 95%CI: 1.15-1.70) had significantly greater odds of POS compared to patients undergoing other types of surgical procedures. Conclusions: Vascular, cardiac, and neurological surgery remained strongly associated with POS in an analysis accounting for the association between patient-level factors and surgical categories.